Effects of Ego-Depletion and State Anxiety on Performance Changes in Dart-Throwing Tasks: A Latent Curve Model Approach Reporting Trial Data for Human Participants - Yang, Jonghyun; Park, Kiwon; Shin, Myoungjin (Frontiers in Psychology, 2019)
This study examined the effects ego depletion (ED) and state anxiety (SA)have on performance changes in dart-throwing, a perceptual-motor task, using a Latent Curve Model (LCM). Twenty-two men, who had never played darts before, were recruited and randomly assigned to two counterbalanced groups: Group A was exposed first to ED and then to non-ED (NED), and Group B was exposed first to NED and then to ED. We found that the number of trials had a non-linear effect on darts performance, which improved as the number of trials increased before declining again; that is, mean radial error decreased first and then increased. Therefore, motor performance was sustained in the form of a quadratic curve as the number of task executions increased. In general, the higher the degree of ED and SA, the greater the negative effect on performance. However, this phenomenon was observed only in the early-phase trials, and the interacting influence of ED and SA appeared in the late-phase trials. Thus, this study demonstrated that ED and SA have direct effects on performance curves in early-phase trials only, and that their interacting influence appears in late-phase trials.